2018
DOI: 10.1101/464966
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probiotic Associated Therapeutic Curli Hybrids (PATCH)

Abstract: 30There is an unmet need for new treatment methods for inflammatory bowel disease (IBD) that 31 can reliably maintain remission without leading to detrimental side effects. Beneficial bacteria 32 have been utilized as an alternative treatment for IBD albeit with low efficacy. We genetically 33 engineered Escherichia coli Nissle 1917 (EcN) to create an anti-inflammatory fibrous matrix in 34 situ. This matrix consists of EcN-produced curli nanofibers displaying trefoil factors (TFFs), 35 known to promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 61 publications
0
26
0
Order By: Relevance
“…In these examples, cells were either combined with synthetic polymers or biopolymers to create composites, or they were designed/selected to produce a specific extra‐cellular matrix (e.g., curli fibers, cellulose). [ 15–30 ] In our recent work, we have shown that this approach can be used to fabricate macroscopic stiff (2‐4 GPa) thin films by exploiting the stiff structural characteristics of curli fibers. [ 31 ] In contrast to the above approaches, we wondered whether living cells alone, without any extracellular matrix, could serve as the primary building block in ELM fabrication and thereby incorporate aspects of self‐regeneration.…”
Section: Evolution and Fabrication Of Slmsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these examples, cells were either combined with synthetic polymers or biopolymers to create composites, or they were designed/selected to produce a specific extra‐cellular matrix (e.g., curli fibers, cellulose). [ 15–30 ] In our recent work, we have shown that this approach can be used to fabricate macroscopic stiff (2‐4 GPa) thin films by exploiting the stiff structural characteristics of curli fibers. [ 31 ] In contrast to the above approaches, we wondered whether living cells alone, without any extracellular matrix, could serve as the primary building block in ELM fabrication and thereby incorporate aspects of self‐regeneration.…”
Section: Evolution and Fabrication Of Slmsmentioning
confidence: 99%
“…[15,16] Additional work has focused on ELMs that function as catalytic surfaces, filtration membranes, under-water adhesives, pressure sensors, conductive films, gut adhesives, etc. [17][18][19][20][21][22][23][24][25][26][27][28][29][30] In spite of rapid progress in the field, it should be noted that there are few examples of ELMs that combine the structure-building capabilities of cells with their other capabilities, like self-regeneration, self-healing, or environmental responsiveness. ELM technologies that can streamline fabrication by relying more on autonomous cellular functions could help advance the field from a fundamental perspective and lead to ELMs compatible with scalable manufacturing techniques.…”
mentioning
confidence: 99%
“…To demonstrate the potential functionality of the capsules, we produced hybrid capsules containing engineered curli nanofibers displaying various functional protein domains. Curli are insoluble and robust functional protein fibers anchored to the surface of E. coli cells, whose versatility as a platform for ELMs has been explored in many applications, including adhesion to abiotic surfaces, [ 16 ] in vivo display of therapeutic domains, [ 45 ] and sequestration of pathogens from drinking water, [ 46 ] among others. [ 47 ] We hypothesized that we could add a range of functionality to the capsules by expressing curli‐tethered proteins, which would remain fixed within the BC matrix while interacting with the external solution.…”
Section: Resultsmentioning
confidence: 99%
“…developed an engineered EcN that generated fibrous matrices to promote mucosal healing for alleviating IBD. [ 118 ] Curli fiber proteins were fused with trefoil factor (TFF) domains to promote epithelial restitution, and the EcN was engineered to create fibrous matrices through the in situ self‐assembly of the modified curli fibers ( Figure A–D). The results demonstrated that the engineered EcN significantly reduced the weight loss of mice, decreased pro‐inflammatory cytokine levels, prevented colon length reduction, and displayed superior anti‐inflammation efficacy in a dextran sodium sulfate (DSS)‐induced colitis model.…”
Section: Emerging Diagnosis and Advanced Therapymentioning
confidence: 99%